Pembuatan Matriks dari Kompleks Polielektrolit Kitosan Pektin untuk Sediaan Tablet Mengapung - Sagita, Erny; Anwar, Effionora; Surini, Silvia (UI Scholars Hub, 2010)
Chitosan is a natural cationic polymer. That cationic property makes chitosan can form polyelectrolite complex (PEC) with anionic polymer. In this research, pectin was used as anionic polymer that interact ionically with chitosan. The aim of this research is to produce and characterize chitosan-pectin PEC that would be used as matrix in floating tablet. The solutions of chitosan and pectin 0,3% w/v were mixed in ratio 1:9, 3:7, 1:1, 7:3 and 9:1 with pH of the solution 4,5 and 5,0. The best condition to produce PEC was in pH 5,0 with ratio of chitosan and pectin = 3:7. The differences between chitosan-pectin PEC characteristic and its origin polymer were shown by functional group analysis, thermal analysis, swelling capacity and gel strength. The PEC was then used as matrix in floating tablet.